Mechanical Characterization and Modeling of the Porcine Cerebral Meninges - Pierrat, Baptiste; Carroll, Louise; Merle, Florence; MacManus, David B.; Gaul, Robert; Lally, Caitríona; Gilchrist, Michael D.; Ní Annaidh, Aisling (Frontiers in Bioengineering and Biotechnology, 2020)
The cerebral meninges, made up of the dura, arachnoid and pia mater, is a tri-layer membrane that surrounds the brain and the spinal cord and has an important function in protecting the brain from injury. Understanding its mechanical behaviour is important to ensure the accuracy of finite element (FE) head model simulations which are commonly used in the study of traumatic brain injury (TBI). Mechanical characterisation of freshly excised porcine dura-arachnoid mater (DAM) was achieved using uniaxial tensile testing and bulge inflation testing, highlighting the dependency of the identified parameters on the testing method. Experimental data was fit to the Ogden hyperelastic material model with best fit material parameters of mu=450 +/- 190kPa and alpha=16.55 +/-3.16 for uniaxial testing, and mu=234 +/- 193 kPa and alpha=8.19 +/- 3.29 for bulge inflation testing. The average ultimate tensile strength of the DAM was 6.91 +/- 2.00 MPa (uniaxial), and the rupture stress at burst was 2.08 +/- 0.41 MPa (inflation). A structural analysis using scattered angle light microscopy (SALS) revealed that while local regions of highly aligned fibres exist, globally, there is no preferred orientation of fibres and the cerebral DAM can be considered to be structurally isotropic. This confirms the results of the uniaxial mechanical testing which found that there was no statistical difference between samples tested in the longitudinal and transversal direction (p=0.13 for mu, p=0.87 for alpha). A finite element simulation of a craniotomy procedure following brain swelling revealed that the mechanical properties of the meninges are important for predicting accurate stress and strain fields in the brain and meninges. Indeed, a simulation using a common linear elastic representation of the meninges was compared to the present material properties (Ogden model) and the intracranial pressure was found to differ by a factor of 3. The current study has provided researchers with primary experimental data on the mechanical behaviour of the meninges which will further improve the accuracy of FE head models used in TBI.